The nature of the literacy coaching experience: exploring teacher-coach relationships in elementary education - Davis, Susan E., author; Timpson, William, advisor; Anderson, Sharon, committee member; Davies, Timothy Gray, committee member; Zimmerman, Toni, committee member (Colorado State University. Libraries, 2011)
While much research indicates that instructional coaching is likely to be a critical component in the implementation of school reform efforts, little research has explored the actual coaching relationship. Using a phenomenological inquiry approach, the language of the personal perceptions of coaching relationships as revealed through in-depth interviews as well as the interactions between literacy coaches and teachers during coaching sessions were analyzed in order to better understand the nature of coaching relationships and the perceptions that coaches and teachers have concerning coaching's impact on student achievement. Phenomenological analysis using Moustakas' (1994) outline of the van Kaam method, was conducted on nine in-depth interviews with coaches and teachers, and six themes were identified and explored. Role analysis (Carspecken, 1996) using an overlay of Killion & Harrison's (2006) roles of coaches and Anderson et al.'s (2001) Revised Bloom's Taxonomy was conducted on the transcripts of six coaching sessions. The metaphors that coaches and teachers use to describe coaching and coaching relationships were also explored. A pilot study was conducted which included three in-depth interviews and video transcripts of two coaching sessions. The pilot data set was used to refine the data collection and analysis procedures that were initially outlined. The understandings gained through an exploration of the descriptions and interactions of coaches and teachers holds the potential to provide a common language to support role clarification for coaches, teachers, administrators, and other stakeholders. Educators and instructional leaders need the language that would empower them to effectively describe the coaching relationship in order to be able to articulate the rationale needed to provide coaching as a potentially powerful professional development context in the current era of accountability. Additionally, a rich description of the coaching relationship that facilitates role clarification, as well as a clearer understanding of the extent to which the work is grounded in student achievement data, serves to aid in the development of guidelines for coaching programs. Suggestions for future research are outlined based on the findings.
Keywords: coaching; literacy coach